Political ethics from an Islamic perspective - Zainuddin Losi (Indonesia Prime, 2018)
Political ethics laid the foundations of the fundamental human beings as humans, and it is, in fact, human individuals and society members. Men are civilized and cultured, and they do not live outside certain cultures and etiquette. Politically inextricably linked with the thinkers of Islam, politically indivisible. The difference is that when Greek thinkers discuss the interconnectedness of it in the realm of moral philosophy, Islamic political thinkers discuss it within the auspices of theology. This is a sign indicating that the issue of political Islam does not separate the argument with religion.